Evaluating small coronary stents with dual-source photon-counting computed tomography: effect of different scan modes on image quality and performance in a phantom - Thomas Stein; Constantin von zur Muhlen; Niklas Verloh; Till Schürmann; Tobias Krauss; Martin Soschynski; Dirk Westermann; Jana Taron; Elif Can; Christopher L. Schlett; Fabian Bamberg; Christopher Schuppert; et al. (Diagnostic and Interventional Radiology)
PURPOSE: The study aimed to assess the feasibility and image quality of dual-source photon-counting detector computed tomography (PCD-CT) in evaluating small-sized coronary artery stents with respect to different acquisition modes in a phantom model. METHODS: Utilizing a phantom setup mimicking the average patient’s water-equivalent diameter, we examined six distinct coronary stents inflated in a silicon tube, with stent sizes ranging from 2.0 to 3.5 mm, applying four different CT acquisition modes of a dual-source PCD-CT scanner: “high-pitch,” “sequential,” “spiral” (each with collimation of 144 × 0.4 mm and full spectral information), and “ultra-high-resolution (UHR)” (collimation of 120 × 0.2 mm and no spectral information). Image quality and diagnostic confidence were assessed using subjective measures, including a 4-point visual grading scale (4 = excellent; 1 = non-diagnostic) utilized by two independent radiologists, and objective measures, including the full width at half maximum (FWHM). RESULTS: A total of 24 scans were acquired, and all were included in the analysis. Among all CT acquisition modes, the highest image quality was obtained for the UHR mode [median score: 4 (interquartile range (IQR): 3.67–4.00)] (P = 0.0015, with 37.5% rated as “excellent”), followed by the sequential mode [median score: 3.5 (IQR: 2.84–4.00)], P = 0.0326 and the spiral mode [median score: 3.0 (IQR: 2.53–3.47), P > 0.05]. The lowest image quality was observed for the high-pitch mode [median score: 2 (IQR: 1– 3), P = 0.028]. Similarly, diagnostic confidence for evaluating stent patency was highest for UHR and lowest for high-pitch (P < 0.001, respectively). Measurement of stent dimensions was accurate for all acquisition modes, with the UHR mode showing highest robustness (FWHM for sequential: 0.926 ± 0.061 vs. high-pitch: 0.990 ± 0.083 vs. spiral: 0.962 ± 0.085 vs. UHR: 0.941 ± 0.036, P = non-significant, respectively). CONCLUSION: Assessing small-sized coronary stents using PCD-CT technology is feasible. The UHR mode offers superior image quality and diagnostic confidence, while all modes show consistent and accurate measurements. CLINICAL SIGNIFICANCE: These findings highlight the potential of PCD-CT technology, particularly the UHR mode, to enhance non-invasive coronary stent evaluation. Confirmatory research is necessary to influence the guidelines, which recommend cardiac CT only for stents of 3 mm or larger.